Cytomegalovirus Cutaneous Infection in an Immunocompromised Patient - Fasanya, Adebayo A (Cureus, 2016)
Cytomegalovirus (CMV), a member of the Herpesviridae family, is an opportunistic infection with a typically benign course in the healthy host but has a more ominous course in the immunocompromised population. CMV infection commonly affects the visceral organs, particularly the respiratory and the gastrointestinal tract. CMV cutaneous lesions are rare and can be easily missed. We present a case of a 76-year-old woman presenting with a diffuse non-pruritic macular lesion with scattered vesicles and bullae, which was initially treated as a varicella zoster virus infection and herpes simplex viral infection, but was later found on biopsy to be due to cytomegalovirus. She has a history of Sjögren's syndrome, interstitial lung disease, and being on chronic immunosuppression therapy. This case highlights the importance of considering CMV infection in the differential diagnosis of vesicular skin lesions in immunocompromised patients. Based on a PubMed search for “cutaneous cytomegalovirus”, “cutaneous CMV”, “cytomegalovirus skin”, and “skin CMV” in material published in the last 20 years (from 1996 to 2016) and reviewing any applicable referenced material outside of those dates, cases of cutaneous CMV are not well documented.